Applied Electromagnetism and Materials - Moliton, André (Springer New York : Imprint: Springer, 2007)
Applied Electromagnetism and Materials picks up where the author's Basic Electromagnetism and Materials left off by presenting practical and relevant technological information about electromagnetic material properties and their applications. This book is aimed at senior undergraduate and graduate students as well as researchers in materials science and is the product of many years of teaching basic and applied electromagnetism. Topics range from the spectroscopy and characterization of dielectrics and semiconductors, to non-linear effects and electromagnetic cavities, to ion-beam applications in materials science.